(untitled) (Applied Biological Research, 2023)
Two cultivars of hot chilli (Capsicum chinense Jacq.) cv. ‘Manipur’ and cv. ‘Assam’ were used to study the impact of elevated carbon dioxide (eCO2) and elevated temperature (eTemp) on some of their reproductive morphological features and anatomy. Hot chilli were grown under carbon dioxide temperature gradient tunnels (CTGT) wherein different concentration of CO2 and temperature were maintained. The study revealed significant variations in pollen number, diameter and viability under variable regimes of eCO2 and eTemp. Highest pollen number, diameter and viability was found in the plant grown under CTGT II. Significant increase in xylem and phloem number in cv. ‘Manipur’ under CTGT II revealed better adaptability of crop due to improved solute transport to the growing regions. Anomaly in flower development was evidenced in CTGT III causing improper fertilization due to elongated and curved stylethat might obstruct fertlization, although a genotypic variation existed. Therefore, hot chilli cv. ‘Manipur’ can be grown under eCO2 (550 ppm) and eTemp (2oC higher than ambient conditions).